Hiv/aids And Shifting Urban China's Sociomoral Landscape: Engendering Bio-activism And Resistance Through Stories Of Suffering - Hood, Johanna (Penerbit Universiti Sains Malaysia (USM Press), 2012)
In this article, I address the lack of research in current scholarship on the impacts China's changing media is having on those who consume messages about HIV and AIDS, and on the political, social, celebrity and corporate activism which have resulted from the improved circulation of knowledge about the virus in society. To do so, I position current ways of understanding the virus, its marketability and the myriad activism that knowledge of the virus encourages, in light of the impact that initial knowledge of HIV and AIDS sufferers in China had when introduced to the general, urban public. I first discuss the fragmented history of the virus in telling AIDS in China. I then turn to the changes in Chinese society, politics, economy and legal fields which followed the media's sudden publication of stories about HIV/AIDS within the country. I argue that the media's introduction of Chinese "AIDS sufferers" (aizibing huanzhe) through local stories of extreme suffering were critical to the broad-based changes and sustained successful bio-activism that followed their publication.